2012
DOI: 10.1139/f2012-055
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of marine fishes at low abundance

Abstract: The recovery of depleted species depends on their population dynamics at low abundance. Classical population growth models, applied widely in fisheries science, assume that per capita offspring production increases as abundance declines (compensation). However, slow or absent recovery by many depleted fishes might reflect unexpectedly weak compensation or the presence of Allee effects (depensation). Using meta-analytical techniques to describe reproductive dynamics, we find considerable variability among 207 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 41 publications
2
78
0
Order By: Relevance
“…This was recently demonstrated by simulations of a density-dependent, stochastic, individual-based model that tracked changes in life history, survival and r realized in Atlantic cod [55]. Following fishing-induced depletions to 0.05N max , the study documented time and probability of recovery to carrying capacity under scenarios of low to negligible fishing mortality in the presence and absence of an empirically documented Allee effect [10]. Both time to recovery and uncertainty of recovery were predicted to increase dramatically in the presence of an Allee effect [55].…”
Section: Temporal Thresholds For Impaired Recoverymentioning
confidence: 76%
See 1 more Smart Citation
“…This was recently demonstrated by simulations of a density-dependent, stochastic, individual-based model that tracked changes in life history, survival and r realized in Atlantic cod [55]. Following fishing-induced depletions to 0.05N max , the study documented time and probability of recovery to carrying capacity under scenarios of low to negligible fishing mortality in the presence and absence of an empirically documented Allee effect [10]. Both time to recovery and uncertainty of recovery were predicted to increase dramatically in the presence of an Allee effect [55].…”
Section: Temporal Thresholds For Impaired Recoverymentioning
confidence: 76%
“…To overcome some of these limitations, a recent metaanalysis was undertaken on 207 marine fish populations (median number of years per time series was 32) that encompassed periods during which many had remained at low abundance (less than 10%N max ), increasing the data resolution at which Allee effects might be evident [10]. Based on the results of a Bayesian hierarchical model (an approach that provides modelling flexibility with no strong assumptions about the relationship between metrics of abundance and r realized ), it was reported that: (i) some species (25 of 104; 24%) exhibit strong compensatory population dynamics (r realized increasing at low N, i.e.…”
Section: Population Thresholds For Impaired Recoverymentioning
confidence: 99%
“…Another recent perspective on the nature of lowabundance dynamics in marine fishes was provided by Keith and Hutchings [16], who did not use S-R models but split S -R observations into discrete population biomass bins, and assessed whether, at very low abundances, standardized recruit-per-spawner ratios reduced when compared with higher abundances [16]. These analyses focused on interspecific differences and found that Atlantic cod provided strongest evidence for an Allee effect, whereas Atlantic herring showed signals for compensatory dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The ones of most concern are thresholds or tipping points (Kelly et al 2015) in either population size or exploitation rate that lead to irreversible changes. Perhaps of the greatest concern are mechanisms known as depensation that can lead to a threshold population size below which the population might never recover (Walters and Kitchell 2001;Hutchings and Reynolds 2004;Keith and Hutchings 2012). Concern about possible low abundance thresholds and the long recovery times to rebuild stocks from low abundance has caused management agencies to attempt to avoid low levels of abundance.…”
Section: Single-species Population Dynamicsmentioning
confidence: 99%